Pengaruh Harga Dan Lokasi Terhadap Kepuasan Konsumen Kota Parepare - Arwin (Journal of Trends Economics and Accounting Research, 2023)
The effect of price and location on consumer satisfaction in Parepare City. The aim of this study was to determine the effect of price and location on customer satisfaction at the Cahaya Ujung Store, Parepare City. The population in this study were 709 people and the purchasing sample value of 88 respondents was calculated using the slovin formula. The analytical method used in this research is a causal descriptive analysis method. The results of the T-test for the price variable show a significant value of 0.000 which is less than the probability value of 0.05 and the t-count value is 4.683 greater with a t-table value of 1.98, so the price variable has a significant effect on customer satisfaction at the Cahaya Ujung Store. The results of the t-test for the location variable show a significant value of 0.001 less than the probability value of 0.05 and the t-count value is 4.382 greater with a t-table value of 1.98, so the location variable has a significant effect on customer satisfaction at Cahaya Ujung Store. In addition, price and location simultaneously have a significant influence on customer satisfaction at the Cahaya Ujung Parepare Store so that the hypothesis can be accepted. This is supported by the calculated F test value of 32.145 > F table 3.10 with a significance value of 0.000 <0.05.